Albumin Profile Albumin and Protein Filtrate of Snakehead Fish - Dewi Kartika Sari; Hafni Rahmawati (TROPICAL WETLAND JOURNAL, 2022)
Background and Objective: Snakehead fish in South Kalimantan waters is the most common type of fish. The utilization is still limited. In general, snakehead fish is for consumption, so it need an effort of diversification of processed fishery products. The aims of this research were: (1) increasing value-added of snakehead fish of processing functional filtrate albumin, (2) determining the best steaming duration toward albumin level and filtrate protein of snakehead fish. Materials and Methods: Ingredients used this albumin filtrate were fresh snakehead fishes and ginger or turmeric. This research used random design completed with a factor which was steaming duration of csnakehead fish albumin filtrate of 30, 60, 90 and 120 minutes. Results: The result of the research showed that the different steaming duration had significant effect toward protein content but it had no significant effect toward filtrate albumin of snakehead fish. Conclusion: It can be concluded that the making of snakehead fish filtrate with steaming duration of 90 minutes obtained the highest albumin and protein content.